Strategies and prospects for biostimulants to alleviate abiotic stress in plants - Ma, Ying; Freitas, Helena; Dias, Maria Celeste (Frontiers in Plant Science, 2022)
Global climate change-induced abiotic stresses (e.g., drought, salinity, extreme temperatures, heavy metals, and UV radiation) have destabilized the fragile agroecosystems and impaired plant performance and thereby reducing crop productivity and quality. Biostimulants, as a promising and eco-friendly approach, are widely used to address environmental concerns and fulfill the need for developing sustainable/modern agriculture. Current knowledge revealed that plant and animal derived stimulants (e.g., seaweeds and phytoextracts, humic substances, and protein hydrolysate) as well as microbial stimulants (e.g., plant beneficial bacteria or fungi) have great potential to elicit plant tolerance to various abiotic stresses and thus enhancing plant growth and performance-related parameters (such as root growth/diameter, flowering, nutrient use efficiency/translocation, soil water holding capacity, and microbial activity). However, to successfully implement biostimulant-based agriculture in the field under changing climate, the understanding of agricultural functions and action mechanism of biostimulants coping with various abiotic stresses at physicochemical, metabolic, and molecular levels is needed. In the light of recent advances in the field of plant-biostimulant interactions, this review attempts to unravel the underlying mechanisms of action mediated by diverse biostimulants in relation to abiotic stress alleviation as well as to discuss the current challenges in their commercialization and implementation in agriculture under changing climate conditions.